Data-driven Digital Transformation and Business Model Innovation in Small and Medium sized Enterprises - Kottonen, Arttu (My University, 2022)
The study of Digitalization has accelerated in the 21st century to a turning point where both scientific literature and practitioners across multiple fields are increasingly discussing about the next step in digitalization of companies and business models, as well as the emergent global phenomena of Digital transformation. Being a relatively new phenomena, there are important implications on especially organizational perspective of Digital Transformation and how especially Small and Medium Sized enterprises could facilitate it by leveraging data as a strategic key resource of business model innovation. This study focuses on finding insights on how SME’s from various fields have taken on the challenge of leveraging data in their business models to digitally transform themselves. These insights focus on the impacts, possibilities and key learnings the participated companies have experienced during a monitored business development program. First, from a theoretical standpoint, this study explores the literature to both define Digital Transformation and distinguish it from other contemporary digital phenomena that are often mixed. In addition, this study suggests a Digital Transformation framework further bringing clarity to the subject and identifying some of the most important elements contributing to the transformation process from an organizational perspective. Secondly, by collecting and analysing qualitative interview data from the participants, the study highlights some of the successful data-driven transformations of Finnish SME’s during the development program, identifying how SME’s can create, deliver and capture value by transforming their business models. The theoretical findings suggest that Digital Transformation is a broad phenomenon affecting the entire company, its strategy, offering, structure etc. Indeed, the literature demonstrates the clear distinction in scope when compared other digital phenomena such as digitization and digitalization. The study suggests that data can be greatly leveraged as a resource in business model innovation practices, further facilitating the digital transformation of a company. Finally, empirical findings provide evidence that data-driven business model innovation can facilitate the transformation of SME’s and that transformation has the potential of bringing massive impacts on the ability to generate new revenue and growth, scale globally as well as adapt to the ever so fluid and challenging digital business landscape.
Keywords: Digital Transformation, Data-driven Business Model Innovation, Small and Medium sized Enterprise